Berry Crop Production and Protection - Debnath, Samir (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
Berry crops include, but are not limited to, the genera: Fragaria (strawberry, Rosaceae), Ribes (currant and gooseberry, Grossulariaceae), Rubus (brambles: raspberry and blackberry; Rosaceae), Vaccinium (blueberry, cranberry and lingonberry; Ericaceae) and Vitis (grapes, Vitaceae). The significant role of these fruits in maintaining human health has increased their popularity and production, dramatically, across the world. This Special Issue of Agronomy covers berry crops in the areas of breeding, genetics, germplasm, production systems, propagation, plant and soil nutrition, pest and disease management, postharvest, health benefits, marketing and economics and other related areas. The aim will be to bring together a collection of valuable articles that will serve as a foundation of innovative ideas for production and protection of health-promoting berry crops in changed environment.